Premarital Sexual Behavior in Youth Detention Center Class I Kupang - Inggrid Y. S. Te; Indriati A. Tedju Hinga; Soleman Landi (Universitas Nusa Cendana, 2020)
Premarital sexual behavior is any behavior driven by sexual desire, whether alone, with the opposite sex, or with the same sex without marital ties. East Nusa Tenggara Province Indonesian Planning Families Association (PKBI) found that 31% of teenagers in Kupang City had sexual intercourse before marriage. The effects of sexual behavior before marriage are unwanted pregnancies and sexually transmitted infections. The purpose of this study was to describe the factors causing premarital sexual behavior in correctional students before undergoing a period of detention at the Youth Detention Center Class I Kupang. This research was descriptively quantitative. The sample was all 34 teenagers at the youth detention center drawn by a total sampling method. The results showed that only 23,5% of respondents had good knowledge about sexuality. The family support of the respondents was sufficient (55.9%). The majority was exposed to internet media (79.4%) and had a negative peer influence on sexuality (78.4%). Furthermore, most of the respondents engaged in a high risk of premarital sexual behavior (79.4%). Relevant authorities should provide correctional students comprehensive education about premarital sexual behavior.